Towards Additive Manufacturing of Tungsten Carbide Using Renewable Resources. (27th April 2016) - Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : Here we present preliminary results towards additive manufacturing of carbides. A biopolymer-metal oxide gel composite composed of iota-carrageenan, chitin and tungsten trioxide (WO3 ) was shaped and heat treated in order to obtain carbide structures. Upon heat treatment of this composite above 900 °C, a porous structure of tungsten carbide (WC) was obtained. The synthesis mechanism of WC was estimated using the result from XRD characterization. The synthesized WC was characterized with SEM, TEM and nitrogen absorption-desorption to investigate the morphology, particle size and pore size distribution. The carbonaceous materials retained the original shape. The ongoing work is on studying the rheology of the gel composites to extrude through additive manufacturing system to obtained 3D printed carbide parts.